2019
DOI: 10.3390/ijerph16132394
|View full text |Cite
|
Sign up to set email alerts
|

Role Stress, Job Burnout, and Job Performance in Construction Project Managers: The Moderating Role of Career Calling

Abstract: This study aims to explore the influence of role stress (role ambiguity and role conflict) on job burnout and job performance in construction project managers in the Chinese construction industry. Based on the JD-R (Job Demands Resources) model, this study introduces career calling as the moderating variable, in order to develop a theoretical model. The theoretical model is then tested with structural equation modeling. This work uses data from 191 owners, contractors, subcontractors, and supervisors in the Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
132
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(149 citation statements)
references
References 102 publications
9
132
1
7
Order By: Relevance
“…Not surprisingly, researchers have found that high performers tend to have stronger professional skills and better career opportunities, as well as tend to be more likely than low performers to be promoted within their organizations [39]. Construction projects are temporary projects involving multi-disciplinary professionals, so the job performances of construction professionals are affected by multiple interdependent processes and tasks [1,4]. In general, the job performance of construction professionals includes task performance, situational performance, and adaptive performance [40].…”
Section: Job Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…Not surprisingly, researchers have found that high performers tend to have stronger professional skills and better career opportunities, as well as tend to be more likely than low performers to be promoted within their organizations [39]. Construction projects are temporary projects involving multi-disciplinary professionals, so the job performances of construction professionals are affected by multiple interdependent processes and tasks [1,4]. In general, the job performance of construction professionals includes task performance, situational performance, and adaptive performance [40].…”
Section: Job Outcomesmentioning
confidence: 99%
“…The results indicate that job positions had a non-significant impact on job outcomes (job position→job satisfaction, −0.012, p > 0.05; job position→job performance, −0.015, p > 0.05). Third, since older construction professionals may respond differently to WFC compared to young construction professionals [1], this study implemented a homogeneity of variance test (WIF (Levene Statistic = 0.801, p > 0.05); FIW (Levene Statistic = 0.367, p > 0.05)). The results show that the assumption of homogeneity of variance was effective, indicating that the response of elderly construction professionals to WFC is the same as that of young construction professionals.…”
Section: Control Variables Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study conducted by Amin, Khattak and Khan(2018) stated that occupational stress is associated with job commitment and satisfaction. The increment in the dissatisfaction level in relation to jobs result in burnout and high turnover rates (Wu, Hu& Zheng, 2019). In addition, the individual performance suffers as well with the increase in absenteeism, weakened decisions, missing deadlines and similar instances (Ratnawat&Jha, 2014).…”
Section: 3) Impact Of Occupational Stress Of Employee Performancementioning
confidence: 99%